The strategic roles of four enzymes in the interconnection between metabolism and oncogene activation in non-small cell lung cancer: Therapeutic implications. (July 2022) - Icard, Philippe; Simula, Luca; Fournel, Ludovic; Leroy, Karen; Lupo, Audrey; Damotte, Diane; Charpentier, Marie Christine; Durdux, Catherine; Loi, Mauro; Schussler, Olivier; Chassagnon, Guillaume; Coquerel, Antoine; et al.
Abstract: NSCLC is the leading cause of cancer mortality and represents a major challenge in cancer therapy. Intrinsic and acquired anticancer drug resistance are promoted by hypoxia and HIF-1α. Moreover, chemoresistance is sustained by the activation of key signaling pathways (such as RAS and its well-known downstream targets PI3K/AKT and MAPK) and several mutated oncogenes (including KRAS and EGFR among others). In this review, we highlight how these oncogenic factors are interconnected with cell metabolism (aerobic glycolysis, glutaminolysis and lipid synthesis). Also, we stress the key role of four metabolic enzymes (PFK1, dimeric-PKM2, GLS1 and ACLY), which promote the activation of these oncogenic pathways in a positive feedback loop. These four tenors orchestrating the coordination of metabolism and oncogenic pathways could be key druggable targets for specific inhibition. Since PFK1 appears as the first tenor of this orchestra, its inhibition (and/or that of its main activator PFK2/PFKFB3) could be an efficacious strategy against NSCLC. Citrate is a potent physiologic inhibitor of both PFK1 and PFKFB3, and NSCLC cells seem to maintain a low citrate level to sustain aerobic glycolysis and the PFK1/PI3K/EGFR axis. Awaiting the development of specific non-toxic inhibitors of PFK1 and PFK2/PFKFB3, we propose to test strategies increasing citrate levels in NSCLC tumors to disrupt this interconnection. This could be attempted by evaluating inhibitors of the citrate-consuming enzyme ACLY and/or by direct administration of citrate at high doses. In preclinical models, this "citrate strategy" efficiently inhibits PFK1/PFK2, HIF-1α, and IGFR/PI3K/AKT axes. It also blocks tumor growth in RAS-driven lung cancer models, reversing dedifferentiation, promoting T lymphocytes tumor infiltration, and increasing sensitivity to cytotoxic drugs.